Sensitivity to Climate and Weather Changes in Euthymic Bipolar Subjects: Association With Suicide Attempts - Di Nicola, Marco; Mazza, Marianna; Panaccione, Isabella; Moccia, Lorenzo; Giuseppin, Giulia; Marano, Giuseppe; Grandinetti, Paolo; Camardese, Giovanni; De Berardis, Domenico; Pompili, Maurizio; Janiri, Luigi (Frontiers in Psychiatry, 2020)
Background. Climate and weather are known to affect multiple areas of human life, including mental health. In Bipolar Disorder (BD), seasonality represents an environmental trigger for mood switches, and climatic variables may contribute to recurrences. Several studies reported seasonal and climatic-related variations in the rate of suicide attempts. Suicide risk is relevant in BD, with approximately 25% of patients attempting suicide. Therefore, this study aimed to assess sensitivity to weather and climatic variations in BD subjects and its relationship with lifetime suicide attempts. Methods. Three hundred fifty-two euthymic BD and 352 healthy control subjects, homogeneous with respect to socio-demographic characteristics, were enrolled. All participants were administered the METEO-Questionnaire (METEO-Q) to evaluate susceptibility to weather and climatic changes. We also investigated the potential relationship between sensitivity to climate and weather and lifetime suicide attempts in BD patients. Results. METEO-Q scores and the number of subjects reaching the cut-off for meteorosensitivity/meteoropathy were significantly higher in BD patients. Within the clinical group, BD subjects with lifetime suicide attempts obtained higher METEO-Q scores, with no differences between BD-I and BD-II. The number of suicide attempts directly correlated with METEO-Q scores. The presence of suicide attempts was associated with the physical and psychological symptoms related to weather variations. Discussion. Our findings support the relevance of sensitivity to weather and climate variations in a large sample of BD subjects and point out the association of this feature with lifetime suicide attempts.